Comparison of Peak Oxygen Uptake Between Upper-Body Exercise Modes: A Systematic Literature Review and Meta-Analysis - Baumgart, Julia Kathrin; Brurok, Berit; Sandbakk, Øyvind (Frontiers in Physiology, 2020)
PURPOSE: To compare peak oxygen uptake (VO2peak) between the asynchronous arm crank ergometry (ACE), and synchronous wheelchair ergometry (WERG), wheelchair treadmill (WTR) and upper-body poling (UBP) mode. METHODS: PubMed, Scopus, CINAHL and SPORTDiscusTM were systematically searched, and identified studies screened based on title, abstract and thereafter full-text. Studies comparing VO2peak between ≥2 of the modes were included. A meta-analysis was performed by pooling the differences in VO2peak between upper-body exercise modes. The quality of the included studies was assessed and the level of evidence (LoE) established for each mode comparison. Meta-regression analyses investigated the effect of total body mass and participant-related characteristics (% of able-bodied participants, % of participants with tetraplegia and % of participants who are wheelchair athletes) on differences in VO2peak between modes. RESULTS: Of the 19 studies included in this review, 14 studies investigated the difference in absolute and body-mass normalized VO2peak between ACE and WERG, and 5 studies examined the differences between ACE and WTR. No significant difference in absolute or body-mass normalized VO2peak was found between ACE and WERG (overall effect ±95%CI: 0.01±0.06L∙min-1 and 0.06±1.2ml∙kg-1∙min-1, both p>0.75; LoE: strong). No significant difference in absolute or body-mass normalized VO2peak was found between testing in the ACE or WTR mode (overall effect ±95%CI: -0.10±0.18L∙min-1 and -1.8±2.5ml∙kg-1∙min-1, both p>0.14; LoE: moderate). Absolute and/or body-mass normalized VO2peak did not differ between WERG and WTR in one study with 13 participants (LoE: limited) and between ACE and UBP in one study with 18 participants (LoE: moderate). In the meta-regression analyses, there was no significant effect of the investigated factors on differences in VO2peak. CONCLUSIONS: The differences between the asynchronous ACE and synchronous WERG propulsion, including possible differences in trunk involvement, do not seem to influence VO2peak. Therefore, ACE and WERG can be used interchangeably to test VO2peak. Possible differences in VO2peak in all other mode comparisons remain unclear due to the wide CIs and limited to moderate LoE.